1992
DOI: 10.1155/1992/545287
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Features of 67 Patients with Clinically Definite Steele-Richardson-Olszewski Syndrome

Abstract: The clinical features of 67 patients with probable Steele-Richardson-Olszewski syndrome have been analysed. Bradykinesia was present in 92.5% of cases at the time of initial assessment and the two commonest presenting complaints were walking difficulties and stiffness. Only 11 patients had a supranuclear gaze palsy when first seen. Forty-nine patients developed cognitive impairment in the course of their illness based on neuropsychological testing. In addition to the classical clinical findings occasional othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…11 SGP is often absent early in the course of the disease with one study reporting supranuclear gaze palsy in only 11/67 patients at initial evaluation and ultimately clinically diagnosed with PSP. 12 Our findings are consistent with the clinical mantra that SGP develops by the time of death in the majority of patients with PSP although we found that a significant minority retained normal eye movements, similar to previous reports in the literature. 13,14 The retrospective nature of our data does not allow us to assess the differential involvement of horizontal vs vertical gaze or of up- vs down-gaze.…”
Section: Discussionsupporting
confidence: 93%
“…11 SGP is often absent early in the course of the disease with one study reporting supranuclear gaze palsy in only 11/67 patients at initial evaluation and ultimately clinically diagnosed with PSP. 12 Our findings are consistent with the clinical mantra that SGP develops by the time of death in the majority of patients with PSP although we found that a significant minority retained normal eye movements, similar to previous reports in the literature. 13,14 The retrospective nature of our data does not allow us to assess the differential involvement of horizontal vs vertical gaze or of up- vs down-gaze.…”
Section: Discussionsupporting
confidence: 93%
“…74 The pattern of deficits is characteristic of the so called "subcortical dementia": with bradyphrenia, executive deficits, forgetfulness (related to retrieval difficulties), visuospatial problems, and frontal lobetype behavioural abnormalities (inertia, stereotyped behaviour, apathy, disinterest, environmental dependency, etc) which are most likely related to denervation of the prefrontal cortex. Mood symptoms of depression and lability have also been described.…”
Section: Progressive Supranuclear Palsy (Steele-richardson-olszweski'mentioning
confidence: 99%
“…Of 67 patients with clinically diagnosed PSP, one (1%) had lid levator inhibition at the first assessment with a disease duration of 2–4 years, whereas 17 (25%) had lid levator inhibition at the final assessment with a disease duration of 3–9 years. 20 In our previous study, difficulty in opening eyes was observed in 0 of 22 (0%) patients with PSP, 1 of 9 (11%) patients with pallido‐nigro‐luysian atrophy (PNLA) Type 1, and 0 of 9 (0%) patients with PNLA Type 2 during the first 2 years of the disease. 21 Moreover, the prevalence of difficulty in opening eyes was significantly higher in patients with PNLA Type 1 than in those with PSP and PNLA Type 2 (5/9 [55.6%] vs. 1/22 [4.5%] and 0/9 [0%], respectively) during the entire disease course.…”
Section: Discussionmentioning
confidence: 93%
“…The prevalence of difficulty in opening eyes may be relatively rare during the early stage of the disease and may vary among pathological subtypes of the PSP spectrum. Of 67 patients with clinically diagnosed PSP, one (1%) had lid levator inhibition at the first assessment with a disease duration of 2–4 years, whereas 17 (25%) had lid levator inhibition at the final assessment with a disease duration of 3–9 years 20 . In our previous study, difficulty in opening eyes was observed in 0 of 22 (0%) patients with PSP, 1 of 9 (11%) patients with pallido‐nigro‐luysian atrophy (PNLA) Type 1, and 0 of 9 (0%) patients with PNLA Type 2 during the first 2 years of the disease 21 .…”
Section: Discussionmentioning
confidence: 99%